Long-term outcomes of community-based intensive care treatment following neurological early rehabilitation– results of a multicentric German study - Bernadette Einhäupl; Danae Götze; Stephanie Reichl; Lina Willacker; Romy Pletz; Thomas Kohlmann; Esther Henning; Lena Schmeyers; Andreas Straube; Rebekka Süss; Steffen Fleßa; Simone Schmidt; et al. (Neurological Research and Practice)
Abstract Background Weaning from mechanical ventilation (MV) and tracheal cannula (TC) during neurological early rehabilitation (NER) is mostly successful. However, some patients leave NER with TC/MV, requiring home-based specialized intensive care nursing (HSICN). Data on medical and demographic characteristics and long-term outcomes of these patients are limited. Methods A multicentric retrospective observational study across five German NER hospitals collected data from neurological patients with TC/MV at discharge. The study aimed to assess patients’ health status at NER discharge, and to identify predictors of post-discharge survival. Survival rates were analyzed using Kaplan-Meier estimates; further predictors of survival post-discharge were analyzed using Cox regression. Results Among 312 patients, the one-year survival rate was 61.9%, decreasing to 38.1% after approximately 4 years. Older age, higher overall morbidity and discharge with MV were associated with an increased likelihood of death, while a longer stay in NER correlated with survival. Conclusions Patients requiring HSICN after discharge from NER have a high mortality rate. Identifying survival predictors may help to identify patients at risk, and thus could be integrated into the decision-making process for NER discharge. The high mortality post-discharge warrants an evaluation of the current post-hospital care model. Optimizing therapeutic care in the HSICN setting may have the potential to reduce mortality and neuro-disability, and enhance the quality of life in these neurologically severely affected patients. Trial registration The trial OptiNIV - Retrospective study of post-hospital intensive care in neurological patients has been retrospectively registered in the German Clinical Trials Register (DRKS) since 28.10.2022 with the ID DRKS00030580.